Engineering Dielectrics Volume IIA Electrical Properties of Solid Insulating Materials: Molecular Structure and Electrical Beha 1983
DOI: 10.1520/stp37838s
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Processes in Polymers

Abstract: The electrical conductivity of polymers must be understood in order to improve their performance as electrical insulators. At the present time, there is a need to produce materials with lower conductivity than is currently available without compromising the desirable mechanical properties in order to satisfy the continuing demand for high-quality communications cables and optical fibers and for low-loss conventional power apparatus and cables. A further requirement will be for better standoffs for superconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 420 publications
1
28
0
Order By: Relevance
“…In Phase I, the time dependence of the absorption current in the nanocomposites is characterized by an exponent b 1 , which is of the order of 0.5. Wintle [54] has indicated that 0 ≤ b n ≤ 2 is consistent with dipole orientation, carrier tunnelling and carrier hopping, while 0 ≤ b n ≤ 1 is consistent with charge injection forming trapped space charge. Roy [28] reported that the absorption current behaviour was independent of electrode materials and sample thickness and suggested that electrode polarization and dipole orientation were unlikely to be the reason for the absorption current, which is in line with the work of Das-Gupta and Brockley [50].…”
Section: Discussionmentioning
confidence: 99%
“…In Phase I, the time dependence of the absorption current in the nanocomposites is characterized by an exponent b 1 , which is of the order of 0.5. Wintle [54] has indicated that 0 ≤ b n ≤ 2 is consistent with dipole orientation, carrier tunnelling and carrier hopping, while 0 ≤ b n ≤ 1 is consistent with charge injection forming trapped space charge. Roy [28] reported that the absorption current behaviour was independent of electrode materials and sample thickness and suggested that electrode polarization and dipole orientation were unlikely to be the reason for the absorption current, which is in line with the work of Das-Gupta and Brockley [50].…”
Section: Discussionmentioning
confidence: 99%
“…Samples of LDPE from Goodfellow (29.7±2% μm thick, density of 0.92 g/cm 3 [6], estimated crystallinity of 50% [7], and a peak fractional mass distribution of ~6·10 3 amu [8,9]) were broken down in a parallel plate geometry under vacuum using a modified [2] ASTM method [10,11]. All samples were cleaned, vacuum baked while in contact with a grounded surface to eliminate absorbed water and volatile contaminants and any residual stored charge, and stored in dry N2 gas prior to testing [8].…”
Section: A Experimental Methods and Typical Resultsmentioning
confidence: 99%
“…The more general equation for the radiation induced conductivity is For most material, is found to be between 0.5 and 1. NUMIT uses , but the other value might fit better to the test data [9], [10]. We tried to minimize the current leakage; there might be some leakage through cabling and feedthrough, which will show up as an increased conductivity in the simulation.…”
Section: B Thin Metal Prototype Testmentioning
confidence: 99%
“…Simulation results using the geometry of the thin-metal-layer prototype.Electron energy of 1 MeV, flux of 65 pA=cm , dark conductivity of 1:0 210 ohm m , and the coefficient of radiation induced conductivity of 2:1 2 10 sec ohm m rad were used.…”
mentioning
confidence: 99%